Sol_11 - 11 ‫תרגיל‬ ‫שרמקוב יוליה‬...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 11 ‫תרגיל‬ ‫שרמקוב יוליה‬ ‫שיטות האינטגרציה יסודיות‬ : ‫1. אינטגרציה של פונקציות ראציונליות‬ ∫x 2 dx dx dt 1 1 =∫ = { t = x + 1, dt = dx} = ∫ 2 = − + c = − + c .1 2 + 2x +1 t t x +1 ( x + 1) ∫x 2 dx dx dx d ( x + 2) =∫ 2 =∫ =∫ = 2 2 + 4x + 5 x + 4x + 4 +1 ( x + 2) + 1 ( x + 2) + 1 ( ) .2 = arctan( x + 2) + c x+2 1 2x + 4 1 2x − 2 + 6 1 2x − 2 dx = ∫ 2 dx = ∫ 2 dx = ∫ 2 dx + − 2x + 2 2 x − 2x + 2 2 x − 2x + 2 2 x − 2x + 2 1 6 1 2x − 2 1 6 ∫ x 2 − 2 x + 2dx = 2 ∫ x 2 − 2 x + 2dx + 2 ∫ x 2 − 2 x + 1 + 1dx = .3 2 ∫x 2 ( ) 1 2x − 2 1 6 1 2 ∫ x 2 − 2 x + 2dx + 2 ∫ ( x − 1) 2 + 1dx = 2 ln( x − 2 x + 2) + 3 ×arctan( x − 1) + c 2 ∫x 2x +1 dx = ln( x 2 + x + 5) + c .4 + x+5 2 x5 x x2 x dx = ∫ xdx − ∫ 4 dx = −∫ dx = { t = x 2 , dt = 2 xdx ∫ x4 + 1 22 x +1 2 x +1 () = 2 2 }= 2 .5 x 1 dt x1 x1 − ∫2 = − arctan t + c = − arctan x 2 + c 2 2 t +1 2 2 22 ∫x ∫x 2 2 x 1 2x dx = ∫ 2 dx = ln( x 2 + 5) + c .6 +5 2 x +5 dx dx dx =∫ 2 =∫ = 2 − 8 x + 25 x − 8 x + 16 + 9 ( x − 4 ) + 32 d ( x − 4) ( ) ( x − 4) + c 1 =∫ = arctan 2 2 3 ( x − 4) + 3 3 1 .7 11 ‫תרגיל‬ ‫שרמקוב יוליה‬ .8 dx dx dx 1 dx = −∫ 2 = −∫ =− ∫ ⇒ 2 5 1 5 1 5 + 8x − 4 x 4x − 8x − 5 4 4 x − ÷ x + ÷ x − ÷ x + ÷ 2 2 2 2 1 A B = + 5 1 5 1 x − ÷ x + ÷ x − ÷ x + ÷ 2 2 2 2 1 5 1 = A x + ÷+ B x − ÷ 2 2 1 1 1 5 x = − ⇒ 1 = B − − ÷⇒ B = − 2 3 2 2 I =∫ 1 5 1 A + ÷⇒ A = 3 2 2 dx 1 dx 1 1 1 1 ⇒I =∫ =− ∫ =− ∫ dx + ∫ dx = 2 5 1 5 1 5 + 8x − 4 x 4 12 12 x − ÷ x + ÷ x− ÷ x+ ÷ 2 2 2 2 1 1 1 ( 2 x + 1) = − ln ( 2 x − 5 ) + ln ( 2 x + 1) + c = ln +c 12 12 12 ( 2 x − 5 ) x= 5 ⇒1= 2 x5 4x x4 2x dx = ∫ ( x 3 − 2 x)dx + ∫ 2 dx = − x 2 + 2∫ 2 dx = ∫ x2 + 2 x +2 4 x +2 .9 x4 2 2 = − x + 2 ln x + 2 + c 4 ( ) .10 1 2 2x − ( 2x − 4) + 3 6x −1 3 ∫ x 2 − 4 x + 13 dx = 3∫ x 2 − 4 x + 13 dx = 3∫ x 2 − 4 x + 133 dx = 2 3 ( 2 x − 4 ) dx + 3 = 3∫ 2 ∫ x 2 − 4 x3 4 + 9 dx = x − 4 x + 13 + ( ( ) = 3ln x 2 − 4 x + 13 + 11∫ ) 1 ( x − 2) 2 + 32 ( ) dx = 3ln x 2 − 4 x + 13 + 2 ( x − 2) + c 11 arctan 3 3 11 ‫תרגיל‬ ‫שרמקוב יוליה‬ .11 x−2 1 2x − 4 1 2x 1 4 1 2x 1 dx = ∫ 2 dx = ∫ 2 dx − ∫ 2 dx = ∫ 2 dx − 2∫ 2 2 dx = 2 +9 2 x +9 2 x +9 2 x +9 2 x +9 x +3 1 2 x = ln x 2 + 9 − arctan + c 2 3 3 ∫x ( ) 4− x 1 2x − 8 1 2 x + 6 − 14 dx = − ∫ 2 dx = − ∫ 2 dx = + 6 x + 10 2 x + 6 x + 10 2 x + 6 x + 10 1 2x + 6 1 =− ∫ 2 dx + 7 ∫ 2 dx = 2 x + 6 x + 10 x + 6x + 9 + 1 .12 1 2x + 6 1 =− ∫ 2 dx + 7 ∫ dx = 2 2 x + 6 x + 10 ( x + 3) + 1 ∫x 2 1 = − ln x 2 + 6 x + 10 + 7 arctan ( x + 3 ) + c 2 x ∫ x + 1 dx = ∫ ( x + 1) − 1 dx = ( x + 1) dx − ∫ x +1 ( x +1 1 ∫ x + 1 dx = x − ln x + 1 + c .13 ) x 2 − 16 + 16 x2 x 2 − 16 1 ∫ x − 4 dx = ∫ x − 4 dx = ∫ x − 4 dx + 16∫ x − 4 dx = .14 1 x2 = ∫ ( x + 4)dx + 16 ∫ dx = + 4 x + 16 ln x − 4 + c x−4 2 ( ) ( ) x2 + 1 − 1 + x x2 + 1 x2 + x x −1 ∫ x 2 + 1 dx = ∫ x 2 + 1 dx = ∫ x 2 + 1 dx + ∫ x 2 + 1 dx = 1 2x − 2 1 2x 1 .15 = ∫ dx + ∫ 2 dx = ∫ dx + ∫ 2 dx − ∫ 2 dx = 2 x +1 2 x +1 x +1 1 = x + ln x 2 + 1 − arctan x + c 2 ( ) x3 x( x 2 + 5) − 5 x x ( x 2 + 5) x ∫ x 2 + 5 dx = ∫ x 2 + 5 dx = ∫ x 2 + 5 dx − 5∫ x 2 + 5 dx = .16 5 2x x2 5 2 = ∫ xdx − ∫ 2 dx = − ln( x + 5) + c 2 x +5 22 3 11 ‫תרגיל‬ ‫שרמקוב יוליה‬ dx dx =∫ ⇒ x + 8x x( x + 8) 1 A B =+ x( x + 8) x ( x + 8) 1 = A( x + 8) + Bx 1 x=0⇒ A= .17 8 1 x = −8 ⇒ B = − 8 dx dx 1 dx 1 dx 1 1 I =∫ 2 =∫ =∫ −∫ = ln x − ln x + 8 + c = x + 8x x( x + 8) 8 x 8 ( x + 8) 8 8 I =∫ 2 1 x = ln +c 8 x+8 x +1 x +1 dx dx = ∫ dx = ∫ 3 x −x x( x − 1)( x + 1) x ( x − 1) 1 A B =+ x( x − 1) x ( x − 1) 1 = A( x − 1) + Bx x = 0 ⇒ A = −1 x =1⇒ B =1 I =∫ I =∫ I =∫ .18 dx dx dx x −1 = −∫ + ∫ = − ln x + ln x − 1 + c = ln +c x( x − 1) x ( x − 1) x 3x + 8 dx = ( x − 2) ( x + 5) 3x + 8 A B = + ( x − 2 ) ( x + 5) ( x − 2 ) ( x + 5) 3 x + 8 = A( x + 5) + B ( x − 2 ) .19 x=2⇒ A=2 x = −5 ⇒ B = 1 3x + 8 dx dx I =∫ dx = 2 ∫ +∫ = 2 ln x − 2 + ln x + 5 + c ( x − 2) ( x + 5) ( x − 2 ) ( x + 5) 4 11 ‫תרגיל‬ ‫שרמקוב יוליה‬ .20 x − 72 2 ∫ x ( x + 4 ) ( x − 3) dx x 2 − 72 A B C =+ + x ( x − 3) ( x + 4 ) x ( x − 3) ( x + 4 ) x 2 − 72 = A ( x − 3) ( x + 4 ) + Bx ( x + 4 ) + Cx ( x − 3) x = 0 ⇒ −72 = −12 A ⇒ A = 6 x = 3 ⇒ −63 = B ×21 ⇒ B = −3 x = −4 ⇒ −56 = C ×28 ⇒ C = −2 x 2 − 72 dx dx dx ∫ x ( x + 4 ) ( x − 3) dx = 6∫ x − 3∫ ( x − 3) − 2∫ ( x + 4) = 6 ln x − 3ln x − 3 − 2 ln x + 4 + c .21 x +6 2 ∫ x ( x − 3) x2 + 6 x ( x − 3) 2 2 dx = A B C + + x ( x − 3) ( x − 3) 2 x 2 + 6 = A ( x − 3) + Bx ( x − 3) + Cx 2 2 3 x = 3 ⇒ 15 = C × ⇒ C = 5 3 1 x =1⇒ B = 3 2 x +6 2 dx 1 dx dx 2 1 5 ∫ x ( x − 3) 2 dx = 3 ∫ x + 3 ∫ ( x − 3) + 5∫ ( x − 3) 2 = 3 ln x + 3 ln x − 3 − ( x − 3) + c x = 0 ⇒ 6 = 9A ⇒ A = .22 5 11 ‫תרגיל‬ ‫שרמקוב יוליה‬ x4 + 8 16 x 2 + 8 I =∫ 3 dx = ∫ xdx + ∫ dx x − 16 x x( x − 4)( x + 4) 16 x 2 + 8 A B C =+ + x( x − 4)( x + 4) x ( x − 4) ( x + 4 ) 16 x 2 + 8 = A( x − 4)( x + 4) + Bx ( x + 4 ) + Cx( x − 4) x = 0 ⇒ 8 = −16 A ⇒ A = − 1 2 33 4 33 x = −4 ⇒ C = 4 16 x 2 + 8 x 2 1 dx 33 dx 33 dx I = ∫ xdx + ∫ dx = − ∫ + ∫ +∫ = x( x − 4)( x + 4) 22x 4 ( x − 4) 4 ( x + 4 ) x=4⇒ B= = x2 1 33 33 − ln x + ln x − 4 + ln x + 4 + c 22 4 4 .23 dx dx =∫ +8 ( x + 2)( x 2 − 2 x + 4) 1 A Bx + C = +2 2 ( x + 2)( x − 2 x + 4) x + 2 ( x − 2 x + 4) ∫x 3 ( ) 1 = A x 2 − 2 x + 4 + ( Bx + C ) ( x + 2 ) x = −2 ⇒ A = 1 12 1 1 x = 0 ⇒ 1 = + 2C ⇒ C = 3 3 1 1 x = 1 ⇒ 1 = + 3B + 1 ⇒ B = − 4 12 1 1 x+ dx 1 dx 12 3 dx = I =∫ =∫ + 2 ( x + 2)( x − 2 x + 4) 12 x + 2 ∫ ( x 2 − 2 x + 4) − = 1 1 2x − 8 1 1 ( 2x − 2) − 6 ln x + 2 − ∫ 2 dx = ln x + 2 − ∫ 2 dx = 12 24 ( x − 2 x + 4) 12 24 ( x − 2 x + 4) ( 2x − 2) 1 1 1 dx ln x + 2 − ∫ 2 dx + ∫ = 12 24 ( x − 2 x + 4) 4 ( x − 1) 2 + 3 1 1 1 ( x − 1) = ln x + 2 − ln x 2 − 2 x + 4 + arctan +c 12 24 4× 3 3 = ( ) 6 11 ‫תרגיל‬ ‫שרמקוב יוליה‬ .24 x − 7x − 3 dx = 2 2 +4 3 ∫ x (x 2 ) x 3 − 7 x 2 − 3 A D Bx + C = + 2+ 2 x x ( x + 4) x2 x2 + 4 ( ) ( ) x 3 − 7 x 2 − 3 = Ax x 2 + 4 + D( x 2 + 4) + ( Bx + C ) x 2 3 4 3 2 3 x − 7 x − 3 = ( A + B ) x + ( D + C ) x 2 + 4 Ax + 4 D A+ B =1 25 D + C = −7 ⇒ C = − 4 4A = 0 ⇒ A = 0 ⇒ B = 1 25 x− x3 − 7 x 2 − 3 31 31 2x 25 1 I =∫ 2 2 dx = − ∫ 2 dx + ∫ 2 4 dx = +∫2 dx − ∫ 2 dx = 4x ( x + 4) 4 x 2 ( x + 4) 4 ( x + 4) x x +4 x = 0 ⇒ −3 = 4 D ⇒ D = − ( = ) 31 25 x + ln( x 2 + 4) − arctan + c 4x 2 8 2 .25 x3 + x − 1 x3 + x − 1 13x + 15 dx = ∫ 2 dx = ∫ ( x − 4 ) dx + ∫ dx = 2 ∫ ( x + 2) 2 x + 4x + 4 ( x + 2) = ∫ ( x − 4 ) dx + ∫ ( x − 4) = 2 13( x + 2) − 11 dx dx dx = ∫ ( x − 4 ) dx + 13∫ − 11∫ = 2 2 ( x + 2) ( x + 2) ( x + 2) 2 + 13ln x + 2 + 11 +c x+2 .26 6 + 8x − x 6 + 8x − x dx = ∫ dx 3 2 + 3x + 2 x x( x + 1)( x + 2) ∫x 2 2 6 + 8x − x2 A B C =+ + x( x + 1)( x + 2) x ( x + 1) ( x + 2 ) 6 + 8 x − x 2 = A( x + 1)( x + 2) + Bx ( x + 2 ) + Cx( x + 1) x = 0 ⇒ 6 = 2A ⇒ A = 3 x = −1 ⇒ B = 3 x = −2 ⇒ C = −7 6 + 8x − x2 dx dx dx ∫ x( x + 1)( x + 2)dx = 2∫ x + 3∫ ( x + 1) − 7∫ ( x + 2 ) = 3ln x + 3ln x + 1 − 7 ln x + 4 + c 7 11 ‫תרגיל‬ ‫שרמקוב יוליה‬ .27 I =∫ 3x + 1 ( x − 5 ) ( x + 3) 3x + 1 = 2 dx = A B C + + x − 5 ( x + 3) ( x + 3) 2 ( x − 5) ( x + 3) 2 3 x + 1 = A ( x + 3) + B ( x − 5) ( x + 3) + C ( x − 5) 2 1 4 x = −3 ⇒ −8 = C ×(−8) ⇒ C = 1 x = 5 ⇒ 16 = 64 A ⇒ A = x = 1 ⇒ 4 = 4 − 16 B − 4 ⇒ B = − I =∫ = 3x + 1 ( x − 5 ) ( x + 3) 2 dx = 1 4 1 dx 1 dx dx ∫ x − 5 − 4 ∫ ( x + 3) + ∫ ( x + 3) 2 = 4 1 1 1 1 x −5 1 ln x − 5 − ln x + 3 − + c = ln − +c 4 4 ( x − 3) 4 x + 3 ( x − 3) .28 ( ) ( ) x 3 + x + ( x − 1) x3 + x ( x − 1) dx = x3 + 2 x − 1 I =∫ dx = ∫ dx = ∫ 3 dx + ∫ 3 3 3 x +x x +x x +x x +x ( x − 1) dx ⇒ = ∫ dx + ∫ x ( x 2 + 1) ( x − 1) x( x + 1) 2 = A Bx + C + x x2 +1 x − 1 = A( x 2 + 1) + ( Bx + C ) x x = 0 ⇒ A = −1 x − 1 = −( x 2 + 1) + ( Bx + C ) x x − 1 = ( −1 + B ) x 2 + Cx − 1 B = 1, C = 1 I = ∫ dx + ∫ ( x − 1) dx = x − ∫ dx ( x + 1)dx 1 2 xdx dx +∫ 2 = x − ln x + ∫ 2 +∫ 2 = x x +1 2 x +1 x +1 x( x + 1) 1 = x − ln x + ln x 2 + 1 + arctan x + c 2 2 ( ) 8 11 ‫תרגיל‬ ‫שרמקוב יוליה‬ .29 I =∫ x (x 2 ) −1 2 dx = ∫ x = x ( x − 1) ( x + 1) 2 2 dx A B C D + + + 2 x − 1 ( x − 1) x + 1 ( x + 1) 2 ( x − 1) ( x + 1) 2 2 2 2 x = A ( x + 1) ( x − 1) + B ( x + 1) + C ( x − 1) ( x + 1) + D ( x − 1) 2 x =1⇒ B = 2 1 4 1 4 x = 0 ⇒ 0 = −A+ C 9 1 x = 2 ⇒ 2 = 9 A + + 3C − ⇒ 3 A + C = 0 ⇒ A = 0 ⇒ C = 0 4 4 x 1 dx 1 dx 1 1 1 1 I =∫ dx = ∫ −∫ =− × +× +c 2 2 2 2 4 ( x − 1) 4 ( x + 1) 4 ( x − 1) 4 ( x + 1) ( x − 1) ( x + 1) x = −1 ⇒ D = − .30 x2 − x + 2 x2 − x + 2 I =∫ 4 dx = ∫ dx x − 5x2 + 4 ( x − 1) ( x + 1) ( x − 2 ) ( x + 2 ) x2 − x + 2 A B C D = + + + ( x − 1) ( x + 1) ( x − 2 ) ( x + 2 ) x − 1 ( x + 1) ( x − 2 ) ( x + 2 ) x 2 − x + 2 = A( x + 1)( x + 2) ( x − 2 ) + B ( x − 1)( x + 2) ( x − 2 ) + +C ( x + 1)( x − 1) ( x + 2 ) + D( x + 1)( x − 1) ( x − 2 ) x = 1 ⇒ 2 = −6 A ⇒ A = − 1 3 2 3 1 x = 2 ⇒ 4 = 12C ⇒ C = 3 x = −1 ⇒ 4 = 6 B ⇒ B = 2 3 2 6 + 8x − x 1 dx 2 dx 1 dx 2 dx I =∫ dx = − ∫ +∫ +∫ −∫ = x( x + 1)( x + 2) 3 x − 1 3 ( x + 1) 3 ( x − 2 ) 3 ( x + 2) x = −2 ⇒ 8 = − 12 D ⇒ D = − 1 2 1 2 = − ln x − 1 + ln x + 1 + ln x − 2 − ln x + 2 + c 3 3 3 3 9 11 ‫תרגיל‬ ‫שרמקוב יוליה‬ .31 x + 2x + 1 7 x + 8x + 1 ( x + 2) 7 x + 8x + 1 I =∫ 3 dx = ∫ ( x + 2) + 3 +∫ 3 dx ÷dx = 2 2 x − 2 x − 3x x − 2 x − 3x 2 x − 2 x 2 − 3x 4 2 2 2 7 x2 + 8x + 1 A B C =+ + 3 2 x − 2 x − 3 x x ( x + 1) ( x − 3) 7 x 2 + 8 x + 1 = A( x + 1)( x − 3) + Bx ( x − 3 ) + Cx( x + 1) x = 0 ⇒ 1 = −3 A ⇒ A = − 1 3 x = −1 ⇒ B = 0 22 x =3⇒C = 3 2 ( x + 2) 7 x2 + 8x + 1 ( x + 2) 2 1 dx 22 dx I= +∫ 3 dx = −∫ + ∫ = 2 2 x − 2 x − 3x 2 3x 3 ( x − 3) = ( x + 2) 2 1 22 − ln x + ln x − 3 + c 2 3 3 : ‫2. אינטגרציה של פונקציות אי- רציונליות‬ .32 1 t t −1 +1 dx = t = x ⇒ t 2 = x ⇒ 2tdt = dx } = 2 ∫ dt = 2 ∫ dt = t −1 t −1 x −1 t −1 1 1 = 2∫ dt + 2 ∫ dt = 2 ∫ dt + 2 ∫ dt =2t + 2 ln t − 1 + c = 2 x + 2 ln x − 1 + c t −1 t −1 t −1 { ∫ { 2 1 dx = 2∫ dx = t = x − 2 ⇒ t 2 = x − 2 ⇒ 2tdt = dx x−2 4+ x−2 ( t + 4 − 4 ) dt = 4 dt − 16 dt = 4t − 16 ln t + 4 + c = 2tdt = 2∫ = 4∫ ∫ ∫t+4 4+t t+4 ∫ 4+ = 4 x − 2 − 16 ln }= .33 x−2 +4 +c { 1 t2 dx = t = 3 x ⇒ t 3 = x ⇒ 3t 2 dt = dx } = 3∫ 3 dt = ∫ x+ 3 x t +t .34 t 3 2t 3 3 3 2 2 = 3∫ 2 dt = ∫ 2 dt = ln t + 1 + c = ln x + 1÷+ c = t +1 2 t +1 2 2 ( 10 ) () 11 ‫תרגיל‬ ‫שרמקוב יוליה‬ x+9 t2 dx = t = x + 9 ⇒ t 2 = x + 9 ⇒ 2tdt = dx } = 2∫ 2 dt = ∫x t −9 t2 − 9 + 9 1 18 t −3 = 2∫ 2 dt = 2 ∫ dt + 18∫ 2 2 dt = 2t + ln +c = .35 t −9 t −3 2× 3 t +3 { x+9 −3 +c x+9 +3 = 2 x + 9 + 3ln .36 ∫ 3 x −1 dx = { t = 6 x ⇒ t 6 = x ⇒ 6t 5 dt = dx ⇒ t 2 = 3 x ⇒ t 3 = x x +1 = 6∫ = 6∫ (t ) −1 t5 2 t3 +1 ( }= ( t − 1) ( t + 1) t 5 ( t − 1) t 5 dt =6 ∫ dt =6∫ 2 dt = ( t + 1) ( t 2 − t + 1) ( t − t + 1) t6 − t5 t6 − t5 t dt = 6 ∫ 2 dt =6∫ t 4 − t 2 − t dt + 6 ∫ 2 dt = 2 t − t +1 t − t +1 t − t +1 ) ( ( ) ) ( ) = 6t 5 6t 3 6t 2 2t 6t 5 2t − 1 + 1 − − + 3∫ 2 dt = − 2t 3 − 3t 2 + 3∫ 2 dt = 5 3 2 5 t − t +1 t − t +1 = 6t 5 2t − 1 1 − 2t 3 − 3t 2 + 3∫ 2 dt + 3∫ 2 dt = 5 t − t +1 t − t +1 ( ) ( ) ( ( ) ) 6t 5 1 − 2t 3 − 3t 2 + ln t 2 − t + 1 + 3∫ dt = 2 5 1 3 t − ÷ + 2 4 6t 5 2t − 1 = − 2t 3 − 3t 2 + ln t 2 − t + 1 + 2 3 arctan +c = 5 3 ( ) ( = ) .37 x ∫ ( 3x − 1) 3x − 1 dx = t 2 + 1 2t 2 t (t 2 + 1) = t = 3 x − 1 ⇒ t 2 = 3x − 1 ⇒ x = ⇒ dt = dx } = ∫ dt = 3 3 9 t3 2 21 2 2 2 2 2(3 x − 2) = ∫ dt + ∫ 2 dt = t − + c = 3x − 1 − +c = +c 9 9t 9 9t 9 9 3x − 1 9 3x − 1 11 11 ‫תרגיל‬ ‫שרמקוב יוליה‬ .38 ∫ 1+ x (t x { dx = t = x ⇒ t 2 = x ⇒ 2tdt = dx ) ( } = 2∫ ) 3 t dt = 1+ t +1 −1 ( t + 1) t 2 − t + 1 1 = 2∫ dt = 2 ∫ dt − 2 ∫ dt = 1+ t 1+ t 1+ t 1 2t 3 2 2 = 2 ∫ t − t + 1 dt − 2∫ dt = − t + 2t − 2 ln t + 1 + c = 1+ t 3 3 ( = 2 ) ( x) 3 3 − x + 2 x − 2 ln x +1 + c .39 1 − x dx 1− x 1− x 1− t2 −4t = t = ⇒ t2 = ⇒x= ⇒ dx = 2 1+ x x 1+ x 1+ x 1+ t 1+ t2 I =∫ = 4∫ ( ( ( ) = 2 t2 t2 dt = 4 ∫ dt 1 + t 2 (t 2 − 1) 1 + t 2 (t − 1)(t + 1) ) ( ) t2 A B Ct + D = + + 1 + t 2 (t − 1)(t + 1) t − 1 t + 1 1 + t 2 t2 ) () = A ( 1 + t ) (t + 1) + B ( 1 + t ) (t − 1) + ( Ct + D ) (t − 1)(t + 1) 2 2 x = −1 ⇒ B = − 1 4 1 4 1 1 x=0⇒0= −D⇒ D = 2 2 15 5 3 x = 2 ⇒ 4 = − + 6C + ⇒ 4 = 4 + 6C ⇒ C = 0 44 2 2 t dt dt dt t −1 I = 4∫ dt = ∫ −∫ + 2∫ 2 = ln + 2 arctan t + c = 2 (t − 1) (t + 1) (t + 1) t +1 1 + t (t − 1)(t + 1) x =1⇒ A = ( = ln ) 1− x −1 1− x 1+ x + 2 arctan +c 1+ x 1− x +1 1+ x 12 11 ‫תרגיל‬ ‫שרמקוב יוליה‬ : ‫3 . אינטגרציה של פונקציות טריגונומטריות‬ 1 1 1 1 ∫ cos x cos 3xdx = 2 ∫ cos 4 xdx + 2 ∫ cos 2 xdx = 8 sin4 x + 4 sin 2 x + c 1 cos a cos b = cos ( a + b ) + cos ( a − b ) 2 1 1 1 .41 1 ∫ cos x sin 3xdx = 2 ∫ sin 4 xdx + 2 ∫ sin 2 xdx = − 8 cos4 x − 4 cos 2 x + c 1 sin a cos b = sin ( a + b ) + sin ( a − b ) 2 .42 1 ∫ cos x cos 3x cos 5 xdx = 2 ∫ (cos 4 x + cos 2 x) cos 5 xdx = 1 1 ∫ cos 4 x cos 5 xdx + 2 ∫ cos 2 x cos 5 xdx = 2 1 cos a cos b = cos ( a + b ) + cos ( a − b ) .43 2 1 1 1 1 = ∫ cos 9 xdx + ∫ cos xdx + ∫ cos 7 xdx + ∫ cos 3dx = 4 4 4 4 1 1 1 1 = sin 9 x + sin 7 x + sin 3 x + sin x + c 36 28 12 4 = ∫ sin 3 xdx = ∫ sin 2 x sin xdx = ∫ (1 − cos 2 x) sin xdx = = { t = cos x ⇒ dt = − sin xdx = − cos x + } = − ∫ (1 − t 2 )dt = − t + t3 +c = 3 cos3 x +c 3 ( ) 1 − sin 2 x cos x cos3 x cos 2 x cos x dx = ∫ dx = ∫ dx = ∫ sin 4 x sin 4 x sin 4 x = { t = sin x ⇒ dt = cos xdx } = ( 1 − t ) dt = 2 =∫ t 4 .44 dt ∫t 4 −∫ dt 11 1 1 = − 3 + +c =− + +c 2 3 t 3t t 3sin x sin x 13 .45 11 ‫תרגיל‬ ‫שרמקוב יוליה‬ ∫ sin x cos xdx = ∫ sin x cos x sin xdx = ∫ ( 1 − cos x ) cos x sin xdx = = { t = cos x ⇒ −dt = sin xdx } = − ∫ ( 1 − t ) t dt = − ∫ ( 1 − t ) t dt = 7 6 6 6 2 236 ( ) 3 ( ) 3 6 236 ( ) = − ∫ 1 − t 2 t 6 dt = − ∫ 1 − 3t 2 + 3t 4 − t 6 t 6 dt = ∫ −t 6 + 3t 8 − 3t 10 + t 12 dt = =− .46 t 7 t 9 3t11 t13 cos7 x cos 9 x 3cos11 x cos13 x +− + +c= − + − + +c 7 3 11 13 7 3 11 13 .47 14 11 ‫תרגיל‬ ‫שרמקוב יוליה‬ I =∫ dx sin xdx sin xdx =∫ =∫ = 2 ( 2 + cos x ) sin x ( 2 + cos x ) sin x ( 2 + cos x ) (1 − cos 2 x) = { t = cos x ⇒ dt = − sin xdx ⇒ −dt = sin xdx} = − ∫ =∫ dt = ( 2 + t ) (1 − t 2 ) dt dt =∫ ⇒ 2 ( 2 + t ) (t − 1) ( 2 + t ) (t − 1)(t + 1) 1 A B C = + + ( 2 + t ) (t − 1)(t + 1) t + 2 t − 1 t + 1 1 = A(t − 1)(t + 1) + B ( 2 + t ) (t + 1) + C ( 2 + t ) (t − 1) x = −2 ⇒ A = x =1⇒ B = 1 3 . 1 6 1 2 dx 11 11 11 ⇒I =∫ =∫ dt + ∫ dt − ∫ dt = 6 t −1 2 t +1 ( 2 + cos x ) sin x 3 t + 2 x = −1 ⇒ C = − 1 1 1 = ln t + 2 + ln t − 1 − ln t + 1 + c = 3 6 2 1 1 1 = ln cos x + 2 + ln cos x − 1 − ln cos x + 1 + c 3 6 2 .48 1 ×dx (sin x + cos x)dx sin xdx dx =∫ =∫ +∫ = 4 4 4 x cos x cos x cos x cos 2 x tan 2 xdx dx =∫ + tan x = { t = tan x ⇒ dt = } = ∫ t 2 dt + tan x = 2 2 cos x cos x 3 3 t tan x = + tan x + c = + tan x + c 3 3 dx ∫ cos 4 2 =∫ 2 2 .49 15 11 ‫תרגיל‬ ‫שרמקוב יוליה‬ dx (sin 2 x + cos 2 x)dx dx dx ∫ sin 2 x cos4 x = ∫ sin 2 x cos 4 x = ∫ cos 4 x + ∫ sin 2 x cos2 x = dx (sin 2 x + cos 2 x)dx dx dx dx =∫ +∫ =∫ +∫ +∫ 2 = 4 2 2 4 2 cos x sin x cos x cos x cos x sin x 3 tan x = { exesise 48} = + tan x + tan x − cot x + c = 3 tan 3 x = + 2 tan x − cot x + c 3 .50 sin x cos x + sin x 1+ 1 + tan x 1 cos x + sin x cos x dx = cos x I =∫ dx = ∫ ∫ 2sin x cos x dx = 2 ∫ sin x cos 2 x dx = sin 2 x 2sin x cos x 1 cos x 1 sin x 1 cos x 1 1 =∫ dx + ∫ dx = ∫ dx + ∫ dx = 2 2 2 2 sin x cos x 2 sin x cos x 2 sin x cos x 2 cos 2 x 1 cos x 1 1 =∫ dx + ∫ dx = { t = sin x ⇒ dt = cos xdx } = 2 2 sin x(1 − sin x) 2 cos 2 x 1 dt 1 1 1 dt 1 1 =∫ +∫ dx = − ∫ +∫ dx ⇒ 2 2 2 t (1 − t ) 2 cos x 2 t (t − 1)(t + 1) 2 cos 2 x 1 A B C =+ + t (t − 1)(t + 1) t (t − 1) (t + 1) 1 = A(t − 1)(t + 1) + Bt (t + 1) + Ct (t − 1) t = 0 ⇒ A = −1 1 t =1⇒ B = 2 1 t = −1 ⇒ C = 2 1 + tan x 1 dt 1 1 ⇒I =∫ dx = − ∫ +∫ dx = sin 2 x 2 t (t − 1)(t + 1) 2 cos 2 x 1 dt 1 dt 1 dt 1 1 =∫ −∫ −∫ +∫ dx = 2 t 4 (t − 1) 4 (t + 1) 2 cos 2 x 1 1 1 1 = ln t − ln t − 1 − ln t + 1 + tan x + c = 2 4 4 2 1 1 1 1 = ln sin x − ln sin x − 1 − ln sin x + 1 + tan x + c = 2 4 4 2 1 1 1 = ln sin x − ln sin 2 x − 1 + tan x + c = 2 4 2 1 1 1 1 1 1 = ln sin x − ln cos 2 x + tan x + c = ln sin x − ln cos x + tan x + c = 2 4 2 2 2 2 1 1 = ln tan x + tan x + c 2 2 16 11 ‫תרגיל‬ ‫שרמקוב יוליה‬ .51 dx x 1− z 2dz ∫ 2 + 3cos x = z = tan 2 ⇒ cos x = 1 + z 2 ⇒ dx = 1 + z 2 = 2dz 2dz 2 dz 1+ z2 = ∫ 1+ z 2 = ∫ = 2∫ = 2 2 2 1− z 2 + 2 z + 3 − 3z 2 + 2 z + 3 − 3z 2 2 + 3× 1+ z2 1+ z2 x tan + 5 dz 1 z+ 5 1 2 = 2∫ = ln +c = ln +c 5 − z2 5 z− 5 5 tan x − 5 2 2 .52 dx ∫ 4 − cos 2 x = { m = 2 x ⇒ dm = 2dx } = 1 dm m 1− z2 2dz = z = tan ⇒ cos m = ⇒ dm = = 2 ∫ 4 − cos m 2 2 1+ z 1+ z2 2dz 2dz 2 1 1 dz 1+ z2 = ∫ 1+ z 2 = ∫ =∫ = 2 2 1− z 2 2 4 + 4z −1 + z 3 + 5z 2 4− 1+ z2 1+ z2 1 dz 1 z 1 5 =∫ = arctan +c = arctan (tan x) + c 5 z2 + 3 3 3 3 15 5× 5 5 5 = .53 ( ( cos x + 2 ) − 2 ) dx = dx − 2 dx = cos xdx =∫ ∫ 2 + cos x ∫ ∫ 2 + cos x 2 + cos x x 1− z2 2dz = z = tan ⇒ cos x = ⇒ dx = = 2 2 1+ z 1+ z2 2dz 2dz 2 dz 1+ z2 = x − 2∫ 1 + z 2 = x − 2 ∫ = x − 4∫ = 2 2 1− z 2 + 2z +1− z 3 + z2 2+ 1+ z2 1+ z2 x tan 4 z 4 2 +c = x− arctan +c = x− arctan 3 3 3 3 17 11 ‫תרגיל‬ ‫שרמקוב יוליה‬ 54 2 + cos xdx dx cos xdx = 2∫ +∫ = sin x sin x sin x x 2z 2dz = z = tan ⇒ sin x = ⇒ dx = = 2 2 1+ z 1+ z2 ∫ = { t = sin x ⇒ dt = cos xdx} = 2dz 2 dt dz dt = 2 ∫ 1 + z + ∫ =2 ∫ + ∫ = 2 ln z + ln t + c = 2z t z t 1+ z2 x = 2 ln tan + ln sin x + c 2 18 ...
View Full Document

This note was uploaded on 01/26/2012 for the course IEM 1911.101.1 taught by Professor Kagnovski during the Spring '11 term at Ben-Gurion University.

Ask a homework question - tutors are online